First Report of Two Cases of Acute Gastric Ischemia after Robot-Assisted Radical Cystectomy - Nikolaos Grivas; Alexander D. Horsch; Esther Wit; Annemarie Bruining; Johanna van Sandick; Henk G. van der Poel (Case Reports in Urology)
Gastrointestinal ischemia is rare after small pelvis surgery. Minimal invasive robotic surgery requires adaptation of the surgical approach for cystectomy and derivation construction such as the use of pneumoperitoneum and Trendelenburg positioning of the patient. Two cases with gastric ischemic complications after robot-assisted radical cystectomy are described. The first case was a 68-year-old female who had prolonged gastroparalysis and blood in a replaced gastric tube at day 10 after robotic cystectomy and Bricker urinary derivation. Gastroscopy revealed ischemia of gastric and proximal duodenal mucosa while computed tomography showed multiple calcifications and thrombi in the coeliac trunk branches and splenic infarcts. The stenosis of the origin of the mesenteric superior artery was stented via an endovascular procedure, and the patient recovered with normal gastroscopy 1 month postoperatively. The second case was a 73-year-old male who developed abdominal pain and fever 5 days after robotic cystectomy and Bricker. On abdominal computed tomography imaging, subcutaneous emphysema, intra-abdominal air, and calcification at the origin of the coeliac trunk were found. At laparotomy 5 days after the cystectomy, a 3 cm hole in the fundus of the stomach was found which was removed with the major stomach curvature. Gastroscopy 5 days after hemigastrectomy revealed no remnant ischemia. The prolonged pneumoperitoneum during robotic cystectomy, the deep Trendelenburg position, and the preoperatively impaired vascular system can be the reasons of our first two cases of gastric ischemia. This rare complication should be kept in mind in patients with symptoms of gastric ischemia since it can result in gastric perforation.